La discussione sulla dignità umana nella bioetica contemporanea (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Recent criticisms of the use of the concept of human dignity in bioethics are discussed. It is argued that the central meaning of human dignity refers to the special value of humanity and human agency, as originally highlighted in Kant’s ethics. It is also argued that, contrary to what is claimed by critics, there are reasons not to accept the reduction of human dignity to autonomy. Examples of this non reducibility of the former to the latter are taken from the cure of demented people and the practice of commercial surrogacy.
Keywords: Human dignity; autonomy; bioethics; dementia; commercial surrogacy